2018 27th IEEE International Symposium on Robot and Human Interactive Communication (RO-MAN) 2018
DOI: 10.1109/roman.2018.8525659
|View full text |Cite
|
Sign up to set email alerts
|

Can(‘t) Wait to Have a Robot at Home? - Japanese and German Users' Attitudes Toward Service Robots in Smart Homes

Abstract: In the present study, we compared Japanese and German participants' perceptions of social robots. To do so, participants from both cultural backgrounds evaluated two types of service robots designed for use in the smart home context. One of the prototypes featured a rather technical appearance, whereas the other prototype featured a newly designed social robot head. Against our predictions, Japanese and German participants evaluated both robot types similarly. Japanese participants generally showed a stronger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…In this case, anthropomorphism had a negative effect on trust. Last but not least, Bernotat and Eyssel [7] could not confirm any impact of anthropomorphism in work-related HRI. The study investigated judgments of an anthropomorphically designed versus a standard industrial (non-anthropomorphic) robot in smart homes.…”
Section: Anthropomorphism In Hrimentioning
confidence: 81%
See 1 more Smart Citation
“…In this case, anthropomorphism had a negative effect on trust. Last but not least, Bernotat and Eyssel [7] could not confirm any impact of anthropomorphism in work-related HRI. The study investigated judgments of an anthropomorphically designed versus a standard industrial (non-anthropomorphic) robot in smart homes.…”
Section: Anthropomorphism In Hrimentioning
confidence: 81%
“…Only few studies have focused on a work-related HRI so far. Whereas an anthropomorphic robot movement seems to support users' perception of predictable robot behaviour [37,46], a positive impact of anthropomorphism on trust in industrial HRI could not be clearly confirmed as results are mixed [3,7]. However, it seems that an anthropomorphic design could lead to a more forgiving attitude when a robot is error-prone [14].…”
Section: :5mentioning
confidence: 99%
“…The cultural background and nationality of users may contribute to the variability in people's attitudes toward [52], trust in [20], and acceptance of [53] social robots. The present review therefore compares the geographical locations (i.e., countries) in which the studies took place as an approximation of participants' cultural backgrounds.…”
Section: Geographical Locationmentioning
confidence: 99%
“…When cultural explanations are taken away, Japanese attitudes towards robots are not necessarily different to anywhere else. For example, a 2018 paper by Jasmin Bernotat and Friederike Eyssel demonstrated that Japanese and German attitudes towards the acceptance of robots in the home were broadly similar, with both groups displaying anxiety towards robots (Bernotat & Eyssel, 2018).…”
Section: Observations and Interviewsmentioning
confidence: 99%